TOTAL QUALITY MANAGEMENT (TQM), JALAN ALTERNATIF MEMPERBAIKI MANAJEMEN PERGURUAN TINGGI (Al'Adalah, 2002)
In this life, changes will never end, and so changes in the implementation of management along with the more complex organizational problems. That's why adoption, creation, and innovation are needed. Total quality management is now widely employed in managing organization and management, including tertiary educational institution that also has three elements (namely; input, process and output) and also places human resources as vital component. Human resources, as a vital component in tertiary level, should get attention and treatment as mentioned in TQM, for example in shared vision, cross-functional cooperation, empowerment and involvement, participative management style, available advanced training and effective communication channel. Thus, the application of TQM is actually one of the efforts to change irrational-traditional management into rational-modern management, one of whose elements is decision making based on fact.